Maternal dietary components in the development of gestational diabetes mellitus: a systematic review of observational studies to timely promotion of health - Lambert, Victoria de Los Milagros (2023)
Background: There is ample evidence that considers diet as an important factor in the prevention of gestational diabetes mellitus (GDM). The aim of this review is to synthesise the existing evidence on the relationship between GDM and maternal dietary components. Methods: We performed a systematic bibliographic search in Medline, Latin American and Caribbean Health Sciences Literature (Lilacs) and the Latin American Nutrition Archive (ALAN) of regional and local literature, limiting the searches to observational studies published between 2016 and 2022. Search terms related to nutrients, foods, dietary patterns and the relationship to GDM risk were used. The review included 44 articles, 12 of which were from America. The articles considered different topics about maternal dietary components as follows: 14 are about nutrient intake, 8 about food intake, 4 combined nutrient and food analysis and 18 about dietary patterns. Results: Iron, processed meat and a low carbohydrate diet were positively associated with GDM. Antioxidant nutrients, folic acid, fruits, vegetables, legumes and eggs were negatively associated with GDM. Generally, western dietary patterns increase GDM risk, and prudent dietary patterns or plant-based diets decrease the risk. Conclusions: Diet is considered one of the causes of GDM. However, there is no homogeneity in how people eat nor in how researchers assess diet in different contextual conditions of the world.